2009
DOI: 10.1253/circj.cj-08-0959
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Valsartan Against Progression of Left Ventricular Dysfunction After Myocardial Infarction

Abstract: Circ J 2009; 73: 918 -924 dvances in coronary care and coronary interventional therapies have reduced the in-hospital mortality rate to less than 10% 1 and improved myocardial remodeling in cases of acute myocardial infarction (AMI). 2 However, AMI patients successfully treated by coronary interventions within a few hours of the onset sometimes develop severe myocardial dysfunction in the chronic stage as a result of myocardial remodeling. Left ventricular (LV) remodeling after AMI limits the long-term prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…20-22 Similar effects of angiotensin receptor blockers have been reported, particularly with the use of valsartan. 23 In-hospital heart failure was also an independent factor associated with in-hospital mortality; it is possible that the effect of absence of BB prescription on the day of admission on in-hospital mortality is explained in part by worse clinical status at admission, particularly heart failure, which limits treatment with BB. Another relevant finding of the present study was that few patients were at target dose at the time of discharge from hospital, with only 34.8% at target for BB, and 21.7% for ACEI.…”
Section: Discussionmentioning
confidence: 99%
“…20-22 Similar effects of angiotensin receptor blockers have been reported, particularly with the use of valsartan. 23 In-hospital heart failure was also an independent factor associated with in-hospital mortality; it is possible that the effect of absence of BB prescription on the day of admission on in-hospital mortality is explained in part by worse clinical status at admission, particularly heart failure, which limits treatment with BB. Another relevant finding of the present study was that few patients were at target dose at the time of discharge from hospital, with only 34.8% at target for BB, and 21.7% for ACEI.…”
Section: Discussionmentioning
confidence: 99%
“…Such ability to prevent ventricular remodeling after AMI has historically been demonstrated mainly in ACE inhibitors, but recent studies have revealed that ARBs are not inferior in this respect. 20 ACE inhibitors do not inhibit angiotensin II, which is produced via an ACEindependent pathway, but can enhance bradykinin accumulation, which results in increased endothelial NO production. ARBs prevent angiotensin II from directly binding to the angiotensin II type-1 receptor.…”
Section: Mmp-9 and LV Remodeling After Amimentioning
confidence: 99%
“…The T-VENTURE Study demonstrated similar effects in the prevention of LV remodeling and clinical events between valsartan and ACEIs in Japanese patients with AMI. 8 In this issue of the Journal, Miyazaki et al have expanded the previous study by prospectively demonstrating that combination therapy with valsartan and trandolapril inhibited LV remodeling compared to monotherapy with either drug in Japanese patients with AMI. 9 This new evidence may be informative for Japanese cardiologists, but we have to stop and consider whether we are allowed to simply conclude that the combination therapy is effective in Japanese patients with AMI.…”
Section: Article P 1158mentioning
confidence: 97%